Kejahatan Penggandaan Profil di Facebook oleh Narapidana sebagai Sebuah Proses Belajar - Bayu Suseno (Antropologi Indonesia, 2019)
Profile cloning scam is one of the cybercrimes developing along with the expanding use of social media through various platforms, including Facebook. As a crime, profile cloning scam is also resulted from a learning process. This article discusses profile cloning scam as a result of a learning process experienced by inmates in prison. It uses primary data collected by observation and in-depth interview from four case studies. Those four studied cases have commonality among them: they were conducted by inmates while serving their terms for other crimes, and they were conducted by duplicating account or stealing identity of law enforcers. The main finding of this study shows that profile cloning scam, as a cybercrime, does not require the mastery of sophisticated skills concerning information technology by its perpetrators beforehand. It opposes established theorization of cybercrime that tends to emphasize the perpetrator’s special skills and also the crime’s characteristics that are systematic and organized. Thereby, instead of emphasizing the sophistication of the crime and the established skill of its perpetrators, this article try to understand profile cloning scam by focusing on its perpetrator’s learning process within the context of prison culture. It includes the importance of understanding of the context and situation within the prison life that enables the learning process takes place.